ADAPTATION OF MARKETING AND LOGISTICS ACTIVITIES OF DAIRY DISTRIBUTION ENTERPRISES TO THE CONDITIONS OF DIGITAL TRANSFORMATION AND WARTIME CHALLENGES - ANDRUSHKEVYCH, Zinayida; KIZENKO, Sergey; ANDRUSHKO, Vitaly (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article is devoted to the topical issues of adapting the marketing and logistics activities of dairy distribution enterprises to the conditions of digital transformation and wartime challenges. The paper analyzes the current state of the dairy industry in Ukraine, key problems, including supply chain disruptions, declining demand, communication instability, and insufficient integration of innovative solutions. The article emphasizes the importance of introducing digital tools, such as CRM systems, e-commerce platforms and omnichannel communications, to improve the efficiency of business processes and strengthen customer relationships..The article substantiates the need for personalization of marketing communications, development of loyalty programs and optimization of logistics processes in the context of digital transformation. The article provides successful examples of implementation of digital solutions by Ukrainian and international companies, which demonstrate their effectiveness in ensuring the sustainability of enterprises in crisis conditions.The study proposes an approach to integrating innovative technologies to create synergies between marketing and logistics processes. The prospects for the development of the industry related to the use of digital tools to expand sales markets, increase competitiveness and meet changing consumer needs are considered. The author emphasizes the importance of implementing adaptive strategies to ensure the sustainable development of enterprises in changing market conditionsThe research materials offer practical recommendations for improving the marketing and logistics activities of dairy distribution enterprises in order to increase their competitiveness, expand their sales markets and strengthen customer loyalty. The results obtained can be used to develop adaptive management models aimed at ensuring the sustainable development of the industry in the face of current economic and social challenges.
Keywords: dairy industry; digital transformation; marketing and logistics activities; CRM systems; omnichannel communications; loyalty programs; supply chains; customer focus; distribution enterprises; sustainable development